Frequency of Leg Pain, Edema, and its Associated Factors among Nurses Working on Shift Duty in Private Tertiary Care Hospital, Karachi - Shakeel Rufan Khokhar; Badil; Raja (Journal of Shalamar Medical & Dental College, 2023)
Background: Long-standing hours cause nurses to be at high risk of lower extremity pain and edema that can lead to varicose veins and deep venous thrombosis.